DINAMIKA PENDIDIKAN ISLAM DI THAILAND - Nuruzzahri, Nuruzzahri (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2023)
The country of Thailand, also known as Muangthai, or Siam, or the land of the white elephant, is located in northern Malaysia, and is often depicted as a flower that blooms on a stalk. Thailand means an independent country, because it is the only country in Southeast Asia that has never been colonized by western powers or other countries in the world. The Muslim population of Thailand is mostly domiciled in the southern part of Thailand, which is an area that is often called Patani, such as in the provinces of Songkhla, Yala, Narathiwat, Setul and its surroundings which historically were part of Daulah Islamiyyah Pattani. In simple terms, Islamic education is education that is "colored" in Islam. So Islamic education is education based on Islam. Thus the values ​​of Islamic teachings really color and underlie the entire educational process. Regarding the spread of Islamic education in Southeast Asia, it cannot be known with certainty, as well as in Patani (South Thailand), but there are several historical records which state that traditional Islamic education began in Patani since the arrival of Islam in Patani land and was then developed by the Patani people for 300 years. years before Raja Patani Sultan Ismail Syah converted to Islam (1488-1511), (Ahmad Omar Chapakia, Malaysia, UKM, 2000: 25). Al-Quran education has promoted education in the form of pondoks. Since then, pondoks have begun to be built in Patani, pondoks have become important and very influential educational institutions and have become a place of support for the community, pondoks are considered a stronghold to defend Malay culture and Islamic religious education. then related to the format of writing in this paper, the author uses this research, which is qualitative research that is literature study (library research). Using books and other literature as the main object. This type of research is research that produces information in the form of notes and descriptive data contained in the text under study.